Communication, networks and computing : first International Conference, CNC 2018, Gwalior, India, March 22-24, 2018, Revised selected papers /: first International Conference, CNC 2018, Gwalior, India, March 22-24, 2018, Revised selected papers. ([2019]) - Unknown
No abstract available